Pembuatan Minuman Soygurt dari Sari Tempe dengan menggunakan bakteri Lactobacillus plantarum - Elizabeth Novi Kusumaningrum (Jurnal Matematika Sains dan Teknologi, 2004)
A study has been conducted to produce soygurt that contain factor-2 isoflavone (6,7,4’- trihydroxy isoflavone), derivat of tempe milk, which was inoculated with Lactobacillus plantarum bacteria. This research consisted of three stages: first was the production of tempe, second was the production of tempe’s milk, and third was the production of soygurt. The production of tempe used single culture of Rhizopus oligosporus and mix culture of Rhizopus stolonifer, Rhizopus oryzae, Rhizopus oligosporus and Rhizopus arrhizus. Protein and lipid content from single culture tempe was 17,28% & 3,92%, whereas in mix culture tempe was 17,24% & 3,96%; in tempe milk using single culture was 3,89% & 2,78%, whereas in mix culture produced 3,79% & 2,58%. Inoculum of Lactobacillus plantarum bacteria in variation of 5%, 7,5%, 10%, 12.5% and 15% v/v in tempe milk were optimized. The measured parameter were pH and formation rate of lactic acid. The best inoculums was 5% v/v. Organoleptic test showed that the best soygurt was soygurt from tempe milk fermentated with single inoculums followed by inoculation with L.plantarum. Protein and lipid content was 3,98% and 2,70%. Thin Layer Chromatography test showed that soygurt contain factor-2 isoflavone useful as antioxidant, antihaemolitic, and antifungi